Конструкція функцій Ляпунова у вигляді пучків квадратичних форм - Грод, I.М.; Кулик, В.Л. (Нелінійні коливання, 2018)
Используя метод знакопеременных функций Ляпунова, исследуется вопрос регулярности линейных расширений динамических систем на многообразиях. Строятся конструкции функций Ляпунова в виде пучков квадратичных форм. By using the method of alternating Lyapunov functions, we investigate the problem of regularity of linear extensions of dynamical systems on manifolds. Structures of Lyapunov functions in the form of pencils of quadratic forms are constructed.